Thermal degradation of polytetrafluoroethylene in flowing helium atmosphere - I. Degradation rate - Jun, H.S.; Kim, K.N.; Park, K.Y.; Woo, S.I. (Springer-Verlag, 1995)
The thermal degradation of polytetrafluoroethylene in flowing helium atmosphere was studied in the temperature range 510-600C. The products of thermal degradation were analyzed by an on-line gas chromatography and the rates of degradation were obtained. At relatively lower temperatures (less than 530°C) the rate curves as a function of time showed two peaks. This phenomenon was explained in terms of diffusion limitation of the gaseous products. Further research was carried out by scanning electron microscopy (SEM) in order to observe the diffusion limitation and these facts were confirmed by observing the matrix of partially degraded polymer. The rate curves which have two peaks indicated that the diffusion limitation was disappeared above ca. 50% conversion. The activation energy in diffusion limitation free region was 78.1 kcal/mole and it was very similar to the result obtained by Madorsky (80.5 kcal/mole). The activation energy was also consistent with that obtained by thermogravimetry. ？ 1995 Korean Institute of Chemical Engineering.